The Cognitive Footprint of Medication Use - Marta Suárez Pinilla; Charlotte R. Stoner; Martin Knapp; Parashkev Nachev; Martin Rossor (Brain and Behavior)
ABSTRACT Introduction The cognitive side‐effects of medication are common, but often overlooked in practice, and not routinely considered in interventional trials or post‐market surveillance. The cognitive footprint of a medication seeks to quantify the impact of its cognitive effects based on magnitude, duration, and interaction with other factors, evaluated across the exposed population. Methods Bayesian multivariable regression analysis of retrospective population‐based cross‐sectional cohorts. Results We replicate positive and negative cognitive effects of commonly used medications in UK Biobank, and extend observed associations to two additional cohorts, the EPIC Norfolk, and the Caerphilly Prospective Cohort. We quantify the resultant cumulative impact at the population level given known patterns of prescribing and compare it with exemplar common diseases. Conclusion The cognitive side‐effects of commonly used drugs may have significant impact at the population level. Consideration should be given to a routine structured assessment of cognition in interventional trials and post‐market surveillance.